2016
DOI: 10.21767/2471-9889.100010
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based Polymeric Materials from Epoxidized Triglyceride and Rosin Derivatives

Abstract: IntroductionBio-based polymers are now moving into the mainstream and may soon be competing with commodity plastics [1-3]. Using biomass as a starting material for plastics is highly significant for reduction of greenhouse gas and fossil resource-saving in social viewpoints, which is one of the most promising solutions to problems concerning global environment and energy resources. Among them, triglyceride oils are expected as an ideal alternative chemical feedstock, since triglyceride oils, derived from plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Rosin is safe for living organisms, and their derivatives are claimed to be nontoxic. They can be used as an alternative to petroleum‐based rigid comonomers due to the presence of large phenanthrene ring 25–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosin is safe for living organisms, and their derivatives are claimed to be nontoxic. They can be used as an alternative to petroleum‐based rigid comonomers due to the presence of large phenanthrene ring 25–28 …”
Section: Introductionmentioning
confidence: 99%
“…They can be used as an alternative to petroleumbased rigid comonomers due to the presence of large phenanthrene ring. [25][26][27][28] The study reported in this manuscript aimed at preparing HFreinforced modified epoxidized soybean oil composites by compression molding technique. The HFs were chemically treated using three different concentrations of aqueous HCl, namely, 0.5%, 0.75%, and 1%.…”
mentioning
confidence: 99%